Early Marriage in the Flexing Era: A Review of Law and Ethics on Social - Hasan, Amir; Hasibuan, Rahyana (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2024)
Early marriage in Indonesia has become a complex and pressing issue, particularly in the context of the digital era known as